Asthma in Primary Care: Making Guidelines Work - Wayne Putnam; Fred Burge; Sue Tatemichi; Peter Twohig (Canadian Respiratory Journal)
OBJECTIVE: To determine the views of family physicians regarding selected asthma recommendations from a Canadian practice guideline and the supporting evidence, and to identify issues needing further development if family physicians are to find guideline recommendations to be truly useful clinical tools.